2010
DOI: 10.1007/s11104-010-0359-5
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene: potential key for biochar amendment impacts

Abstract: Significant increases in root density,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
182
5
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(191 citation statements)
references
References 33 publications
(34 reference statements)
1
182
5
3
Order By: Relevance
“…Kamman et al [54] included wetting-drying cycles (assumed to stimulate microbial N 2 O production), while measuring biomass yields and inorganic-N, observing that increased plant growth correlated with reduced N 2 O emissions in the biochar treatments. A detailed examination of mechanisms for reduced N 2 O emissions from biochar-amended soils was also carried out by Spokas et al [64] who showed the origins and effects of ethylene on N 2 O emissions and its role in reducing N 2 O emissions. The effect that ethylene has on N 2 O production from biochar amended soils needs to be investigated in more detail to further elucidate its role in biochar-N 2 O dynamics.…”
Section: Mitigation Of Nitrous Oxide Emissions Using Biocharmentioning
confidence: 99%
See 1 more Smart Citation
“…Kamman et al [54] included wetting-drying cycles (assumed to stimulate microbial N 2 O production), while measuring biomass yields and inorganic-N, observing that increased plant growth correlated with reduced N 2 O emissions in the biochar treatments. A detailed examination of mechanisms for reduced N 2 O emissions from biochar-amended soils was also carried out by Spokas et al [64] who showed the origins and effects of ethylene on N 2 O emissions and its role in reducing N 2 O emissions. The effect that ethylene has on N 2 O production from biochar amended soils needs to be investigated in more detail to further elucidate its role in biochar-N 2 O dynamics.…”
Section: Mitigation Of Nitrous Oxide Emissions Using Biocharmentioning
confidence: 99%
“…Volatile organic compounds associated with a biochar or ethylene production can decrease nitrification activity [62,64]. In agricultural ecosystems, the lack of positive effects from adding biochar on net nitrification rates may be because agricultural ecosystems are already characterised by high nitrification rates [80].…”
Section: Impacts Of Biochar On Nitrogen Mineralization Immobilisatiomentioning
confidence: 99%
“…Biochar is typically alkaline, highly porous and has a high cation exchange capacity (CEC) and large specific surface area (Downie et al 2009). Adding biochar to soils has been demonstrated to depress N 2 O emissions and to sometimes affect CO 2 from soils by affecting soil pH, aeration (Yanai et al 2007;Van Zwieten et al 2010) and available NH 4 + and NO 3 - (Spokas et al 2010). Furthermore, biochar can capture the NH 3 produced in anthropogenic emissions and make it bioavailable in soils (Taghizadeh-Toosi et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It reflects the higher lignin content of wood, which preferentially forms char during pyrolysis [21]. The minimum values of H/C org and O/C org indicate a high biochar C stability [32][33][34][35], and thus, a maximum potential for C sequestration. H/C org and O/C org ratios of biochars produced from the 45 pyrolysis tests significantly varied for a single biomass, depending on the pyrolysis operating parameters (Tables A1-A3).…”
Section: Analysis Of Biomassmentioning
confidence: 99%